Studi Analisis Parameter Gempa Bengkulu Berdasarkan Data Single-Station dan Multi-Station serta Pola Sebarannya - Hadi, Arif Ismul; Suhendra, Suhendra; Efriyadi, Efriyadi (BERKALA FISIKA, 2010)
Abstract The purpose of this research is to analyze of tectonic earthquake parameter value in Bengkulu Province based on single-station data of BMKG Kepahyang, Bengkulu and multi-station data of BMKG Center, Jakarta along with determine its distribution model from January 2005 until March 2009. The results show that distance difference of mean earthquake epicenter is 28.60 km. The distribution of earthquake in Bengkulu Province from January 2005 until March 2009 had majority distributed in Hindia Oceanic and its mean earthquake included shallow earthquake (<70 km). Â  Keywords: Earthquake parameter, single-station, multi-station, magnitude, and epicenter.Â Â